Serological identification of SARS-CoV-2 infections among children visiting a hospital during the initial Seattle outbreak - Adam S. Dingens (Nature Portfolio, 2020)
COVID-19 disease is less common in children than adults, but the extent to which SARS-CoV-2 infections are missed through symptom-driven testing is not well understood. In this study, the authors show that approximately 1% of children seeking care for reasons other than COVID-19 at a Seattle hospital in March/April 2020 were seropositive for SARS-CoV-2.